Zheng He's Art of Collaboration : Understanding the Legendary Chinese Admiral from a Management Perspective - Hum, Sin Hoon (Singapore : ISEAS Pub. : International Zheng He Society, 2012)
"Know your enemies, know yourself", advised Sun Zi in his famous Art of War (AoW). In contrast, the legendary Admiral Zheng He would have said, "Know your collaborators, know yourself", and this would be the essence of his Art of Collaboration (AoC). This book offers a fresh new approach to doing business and providing leadership in the twenty-first century, where Zheng He's peaceful and win-win collaborative paradigm present in his AoC provides an alternative to the aggressive and antagonistic mindset inherent in Sun Zi's AoW. The author has culled from the existing literature on the historical, cultural, diplomatic, and maritime-oriented Zheng He, connected the dots of his discovery of a managerial Zheng He, and wrote this book to present both the big message of Zheng He's Art of Collaboration as well as an understanding of Zheng He's specific work as a leader and manager.
Title from publisher's bibliographic system (viewed on 24 Nov 2015).
Keywords: Zheng, He, -- 1371-1435.; Admirals -- China -- Biography; China -- History -- Ming dynasty, 1368-1644.